2006
DOI: 10.1590/s1806-83242006000100011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the surgical operating microscope in locating the mesiolingual canal orifice: a laboratory analysis

Abstract: The aim of this study was to evaluate the influence of using the surgical operating microscope (SOM) for detection of the mesiolingual (ML) canal orifice in extracted first maxillary permanent molars. One hundred and eight human first maxillary permanent molars were randomly selected and mounted onto a dental chair mannequin. Conventional access cavity was prepared and an attempt was made to locate the mesiolingual canal orifice using only a sharp explorer, a mirror and a #10 K-file. A mesiolingual canal orifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…Buhrley et al [12] also detected an increased number of mesiobuccal canals with the help of dental loupe and SOM. Previous authors also suggested that magnification and illumination increased the detection rate of root canal orifices [8,13,14]. The use of ophthalmic dye increased the results from 50% (SOM) to 52%.…”
Section: Discussionmentioning
confidence: 92%
“…Buhrley et al [12] also detected an increased number of mesiobuccal canals with the help of dental loupe and SOM. Previous authors also suggested that magnification and illumination increased the detection rate of root canal orifices [8,13,14]. The use of ophthalmic dye increased the results from 50% (SOM) to 52%.…”
Section: Discussionmentioning
confidence: 92%
“…Ultrasonic tips were used to clean the isthmus and grooves, and ultrasonic agitation of the irrigants was applied to maximize the root canal disinfection. Several studies have reported that the combined use of magnification and CBCT images significantly enhanced the success of root canal treatment and retreatment [ 33 , 34 ]. Meanwhile, some concepts such as champagne test, color roadmap and white line test could be useful to find untreated canals in root canal retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…With routine use of the DOM, specific instruments are necessary to increase the clinical procedure's efficiency and effectiveness. The higher magnification and illumination can be used for locating supernumerary canals and improving the discovery of root canal orifices [ 17 ]. Studies have shown that the combined use of magnification and CBCT images significantly facilitates the location and negotiation of root canals in upper molars [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%